Historical Source Study Of The Construction Of Orthodox Churches In Turkestan - Abduvakhidov Dilshod Narbotirovich (Open Academia, 2026)
The article analyzes the history of the construction of Orthodox churches in Turkestan from the perspective of source studies. Based on archival documents, diocesan reports and memoir sources, the territorial distribution of churches, missionary activity and their role in imperial politics are studied. The study uses historical-critical, contextual, comparative and postcolonial methods, interpreting churches not only in a religious, but also in a cultural and political context
Keywords: Turkestan; Orthodox Churches; Colonial Policy